Correction: An electric-field induced dynamical state in dispersions of charged colloidal rods. Issue 14 (14th April 2015) - Dhont, Jan K. G.; Kang, Kyongok
<x xml:space="preserve">Abstract</x> Correction for 'An electric-field induced dynamical state in dispersions of charged colloidal rods' by Jan K. G. Dhont et al., Soft Matter, 2014, 10, 1987–2007.